The Inheritance of Human Traits in the Qur’an Based on the Scientific Interpretation of Zaghlūl Rāghib Muḥammad an-Najjār - Juhrah M. Arib; Nikmatul Khairiyah; M. Suryadinata; Sabil Mokodenseho (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This article aims to analyze the inheritance of human traits in the Qur’an, specifically at Surah An-Nisa verse 1, based on the scientific interpretation of Zaghlūl an-Najjār. This study discusses Zaghlūl an-Najjār because he is a geologist and Muslim scholar who has written many books related to science in the Qur’an. The type of this study was qualitative research with a descriptive method. Primary data were obtained through library research related to the works of an-Najjār and interpretations of the Qur’an and hadith, while articles and books were used as secondary data. The employed research approaches were the character approach to study the history, ideas, and socio-historical conditions of Zaghlūl an-Najjār, the exegesis approach to study the content of the Qur’an, and the scientific approach to understand and reveal the meaning of the verses of the Qur’an. This study concludes that the inheritance of human traits in the Q.S. An-Nisa’ verse 1 according to Zaghlūl an-Najjār is in the words “al-nafs al-wāḥidah” (one soul), which means all humans come from the first created creatures, namely Adam. Likewise, the creation of Eve is explained in the words “wa khalaqa minhā zaujahā” (and We created his wife from himself).